2018
DOI: 10.30685/tujom.v3i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Do the Effects of Brand Personality Dimensions on Brand Loyalty Change According to Consumers? Personalities?

Abstract: Mobile phones, especially the smart ones are becoming a main need for millions of people from all ages. Producers pay attention to develop a repeat purchasing behavior among their customers, aiming to resale their updated models. Brands play an important role in facilitating and affecting customer’s choice process, especially for high-technology products. Brand loyalty concerns the behavior of rebuying and at the same time, the antecedents causing that actual behavior. This study aims to study the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These moderators fall into six themes: consumer-related, brand-related, product-related, company-related, demographics and others (see Table 9). The consumer-related factors, such as consumer ethnocentrism (Supphellen and Grønhaug, 2003), consumer personality (Tuzcuoglu et al , 2018) and consumer-brand congruity (Wang et al , 2009) positively moderated the relationship between BP and its consequences. Similarly, brand-related factors, such as brand attractiveness (Hayes et al , 2006), brand identification (Chung and Park, 2015) and brand endorser (Ambroise et al , 2014) strengthened the relationship of BP with its consequences.…”
Section: Thematic Analysis and Synthesismentioning
confidence: 99%
“…These moderators fall into six themes: consumer-related, brand-related, product-related, company-related, demographics and others (see Table 9). The consumer-related factors, such as consumer ethnocentrism (Supphellen and Grønhaug, 2003), consumer personality (Tuzcuoglu et al , 2018) and consumer-brand congruity (Wang et al , 2009) positively moderated the relationship between BP and its consequences. Similarly, brand-related factors, such as brand attractiveness (Hayes et al , 2006), brand identification (Chung and Park, 2015) and brand endorser (Ambroise et al , 2014) strengthened the relationship of BP with its consequences.…”
Section: Thematic Analysis and Synthesismentioning
confidence: 99%
“…On the other hand, excitement had positive effects for Apple and negative effects for Samsung. This variation is explained by different characteristics of Samsung and Apple mobile phone users (Tuzcuoglu et al, 2018).…”
Section: Loyaltymentioning
confidence: 99%
“…Several studies indicated that consumers are going to choose brands that match their personality the most (Seimiene, 2012;Tan et al, 2016;Tuzcuoglu et al, 2018). Seimiene (2012) in her theoretical model of emotional connection between brand and consumer personalities concluded that the main traits of both brand and consumer personalities should be similar; in that way consumers will more likely choose a certain brand.…”
Section: Brand Personalitymentioning
confidence: 99%